ANALISIS KESALAHAN PESERTA DIDIK KELAS VII SMPN 22 PADANG DALAM MENYELESAIKAN SOAL-SOAL MATEMATIKA BERDASARKAN TAKSONOMI SOLO - Dwi Putri Amilia (Departemen Matematika, 2019)
This study aims to describe the mistake of students in solving mathematical questions in social arithmetic material based on the taxonomy of SOLO. The errors studied were based on the types of Subanji and Mulyoto errors which included conceptual errors, errors using data, errors in interpretation of language, technical errors, and errors in conclusions. Preparation of test questions and response levels of students based on the level of the problem on the SOLO taxonomy. This research is a descriptive study with ten research subjects in class VII.1 of SMPN 22 Padang. Details of subject taking were three subjects with high mathematical abilities, four subjects with moderate mathematical abilities, and three subjects with low mathematical abilities. The results obtained by the subject tend to do (a) conceptual errors including errors in using formulas, errors in understanding the intentions of statements in the questions, errors in determining the right steps to solve the problem, (b) errors using data include not using data should be used in solving problems, (c) errors in interpretation of language include errors in writing information on the question, (d) technical errors involving calculation errors, (e) errors in conclusions include concluding an invalid statement with logical reasoning. The causes of these errors are not skilled in using formulas, not through, and habits of students who do not repeat the lesson.Keywords - Error Analysis, Subanji and Mulyoto Error Types, SOLO Taxonomy